Application Cumulative Tensile Explosions for Roof Cutting in Chinese Underground Coal Mines - Yang, Jun; Liu, Binhui; Bian, Wenhui; Chen, Kuikui; Wang, Hongyu; Cao, Chen (Archives of Mining Sciences, 2021)
Cumulative blasts are an important controlled blasting method used to control the propagation of cracks in the predetermined direction. However, traditional cumulative blasts are associated with long processing times and poor blasting effects. A simple blasting technology called bilateral cumulative tensile explosion (BCTE) is proposed in this paper. There are two application types where BCTE is used. The first application is used to control the stability of high-stress roadways in both Wangzhuang mine 6208 tailgate and Hongqinghe mine 3-1103 tailgate. The second application is used to replace the backfill body in gob-side entry retaining (GER) in Chengjiao mine 21404 panel, Jinfeng mine 011810 panel and Zhongxing mine 1200 panel. The first application type reveals that BCTE can significantly reduce the deformation of the surrounding rock and reduce the associated maintenance cost of the roadways. Whereas the second application type, the roadway deformations are smaller, the process is simpler, and the production costs are lower, which further promotes GER and is of significance towards conserving resources.
Keywords: cumulative blast; bilateral cumulative tensile explosion; roof cutting and pressure relief technology; gob-side entry retaining